Automated prototype for the filling and capping of plastic bottles - Velásquez Costa, José (2017)
This paper describes the implementation of an automated prototype for the filling and capping of plastic bottles, in order to increase the quality level of the products as well as the productivity in the bottling of the bottles. The prototype has been developed with pneumatic actuators, sensors, solenoid valves, solenoids, motors and a programmable logic controller (PLC S7-1200) as well as a gin wheel so that it can control the process automatically, reducing the bottlenecks And allowing uniform filling. For the implementation of the project, the mechanical part was connected to the pneumatic and electrical part.